International Centre for Settlement of Investment Disputes: Investasi Asing dan Jaminan Hukum di Indonesia - Nafs, Tazkiya An (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
Foreign Direct Investment (FDI) is one of the forms of international investment that has significantly contributed to the prosperity of the host country. However, with the growth of the economy, investment disputes have been on the rise, involving both investors and the host government. While Undang-Undang Nomor 25 Tahun 2007 provides sufficient legal safeguards to address potential conflicts between investors and the government, host countries often find it necessary to enter into specific agreements. Undang-undang Nomor 5 Tahun 1968, which ratified the ICSID (International Centre for Settlement of Investment Disputes) Convention, as a means to protect foreign investors from conflicts with the Indonesian government. This convention serves as a mechanism for dispute resolution and as an international policy instrument to promote economic development. The objective of this research is to elucidate the role and benefits of ICSID arbitration in resolving investment disputes in developing countries and to explain the mechanisms and procedures applied in resolving such disputes. This paper is the result of normative legal research, which examines legal rules relevant to the subject matter. ICSID aims to balance the interests of host states and foreign investors, offering an efficient mechanism for settling legal disputes in the field of foreign direct investment. The ICSID agreement essentially establishes the authority of ICSID to resolve disputes based on the written agreements of the parties involved.